Modeling of Astrocyte Networks: Toward Realistic Topology and Dynamics - Verisokin, Andrey Yu.; Verveyko, Darya V.; Postnov, Dmitry E.; Brazhe, Alexey R. (Frontiers in Cellular Neuroscience, 2021)
Neuronal firing and neuron-to-neuron synaptic wiring are currently widely described as orchestrated by astrocytes — elaborately ramified glial cells tiling the cortical an hippocampal space into non-overlapping domains, each covering hundreds of individual dendrites and hundreds thousands synapses. A key component to astrocytic signaling is the dynamics of cytosolic Ca2+ which displays multiscale spatiotemporal patterns from short confined elemental Ca2+ events (puffs) to Ca2+ waves expanding through many cells. Here we synthesize the current understanding of astrocyte morphology, coupling local synaptic activity to astrocytic Ca2+ in perisynaptic astrocytic processes and morphology-defined mechanisms of Ca2+ regulation in a distributed model. To this end, we build simplified realistic data-driven spatial network templates and compile model equations as defined by local cell morphology. The input to the model is spatially uncorrelated stochastic synaptic activity. The proposed modeling approach is validated by statistics of simulated Ca2+ transients at a single cell level. In multicellular templates we observe regular sequences of cell entrainment in Ca2+ waves, as a result of interplay between stochastic input and morphology variability between individual astrocytes. Our approach adds spatial dimension to the existing astrocyte models by employment of realistic morphology while retaining enough flexibility and scalability to be embedded in multiscale heterocellular models of neural tissue. We conclude that the proposed approach provides a useful description of neuron-driven Ca2+-activity in the astrocyte syncytium.